Trace Matriks Simetris Berbentuk Khusus 6×6 Berpangkat Bilangan Bulat - Rugayah, Siti; Anggraini, Daz Vholasky; Praptasari, Mutiara; Pratiwi, Theysa Sahlani (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Suppose is a special symmetric matrix of order 6×6 with integer powers, where the entries are real number elements. To obtain the general form of the trace of the matrix by determining the general form of the matrix A_n^6 where the rank of the matrix is ​​first sought from the power of two to eleven and the power of negative two to negative eleven. Then guess the general formula for the exponent of the matrix with positive integer powers which is proven by mathematical induction and with the same steps guess the formula for the exponent of the matrix with negative integer powers which will be proven by the matrix inverse rule. So that the result is obtained, namely the general form of the trace of the matrix and is proven by the definition of trace along with examples of applications of the trace matrix.